ЭЛЕКТР ЭНЕРГИЯСИНИ ТАҚСИМЛАШ МАСАЛАСИНИ ЕЧИШНИНГ ДАСТУРИЙ ТАЪМИНОТИНИ ИШЛАБ ЧИҚИШ - Утеулиев, Н.У.; Оринбаев, А.Б. (SCIENCE and SOCIETY, 2023)
The article is devoted to the development of a mathematical model for the problem of power distribution and the development of software in the Python programming language for solving algorithms. With the help of the program was found, numerical experiments which carried out and the optimal solution.